Development of Blended Learning Media Based on Openedx Integrated PBL on Rotational Dynamics Material - Aprilia, Nadia; Syahril; Azhar (Postgraduate, University of Mataram, 2024)
Learning physics, especially rotational dynamics, is often difficult for many students because of the complexity of the concepts and abstract approach. In situations like this, conventional physics learning often encounters obstacles to providing in-depth understanding to students. Transformation in the world of education is becoming increasingly important, significantly increasing student motivation in studying physics so that it can improve students' performance. To address this issue, open-source blended learning materials that include problem-based learning (PBL) in the Rotational Dynamics curriculum must be developed. The goals of this study are to identify the phases involved in the creation of learning media; identify appropriate standards for learning media; and assess the usefulness of the learning media under development. The development model known as ADDIE is the process utilized for development. Four experts validated the blended learning media developed and underwent revisions to obtain suitable results. This research shows that: the learning materials created have been deemed legitimate and fit for use in the educational process, with a very high category; The application of the learning materials created is user-friendly and practical, also with a very high category.